Assessing the Northern Gulf of Guinea Coastal Upwelling from a Coastal Weather Station - Toualya, Elisée; Wango, Ted Edgar; Silué, Marcel (European Journal of Applied Sciences, 2022)
A weather station installed sufficiently close to the sea and satellite Sea surface temperature (SST) data have been used to estimate the potentiality of this station to capture the seasonal coastal upwelling signal along the northern coast of the Gulf of Guinea (GG). The mechanism sustaining this idea is the sea breeze prevailing for many months would transport the atmospheric air cooled by the upwelling from the ocean to this weather station. This study has shown that this mechanism is verified the whole year and mainly during the upwelling period sustaining the use of this equipment inland to capture the signal of this upwelling. The variability of the coastal ambient air temperature recorded by the weather station reflects quite well the variability of SST and the cooling of SST due to the upwelling. The seasonal SST and air temperature cooling are observed during the same period with SST colder than air temperature at the peak of the upwelling. Meanwhile, the difference between the two minima is less than 1°C. The signals of air temperature at the weather station and the SST show that the beginning of the cooling of air is triggered by the decrease of solar irradiance and, later the cooling of air is enhanced by the coastal upwelling through its impact on the marine atmospheric boundary layer. This suggests also that the coastal upwelling starts with the decrease of the solar irradiance and enhanced by marine subsurface processes.